Consumer-Directed Health Care: Can Consumers Look After Themselves? - Daniel McFadden; Joachim Winter; Florian Heiss (Swiss Journal of Economics and Statistics, 2008)
In health care systems today, including those of Switzerland and the United States, participants do not necessarily see the big picture of lifetime health costs and quality of life, and in many systems consumers and providers lack the incentives to manage preventative and chronic care to minimize lifetime private and social health costs. Resource allocation problems induced by asymmetric information and misaligned incentives are exacerbated if consumers fail to have the acuity or perspective needed to make choices consistent with their self-interest when faced with complex health care choices with ambiguous future consequences. This paper examines rationality of consumers' health perceptions and choices using as a natural experiment the recent introduction in the United States of a highly subsidized market for prescription drug insurance, and draws lessons from this experiment on the practicality of "Consumer Directed Health Care" as an approach to achieving efficient allocation of health care resources by confronting consumers with the full marginal costs of the services they use.
Keywords: C25; C61; C81; D12; D91; H51; I10; I12; I18; 330; prescription drugs; health insurance; Medicare Part D